Structural and ferroelectric properties (1-x)(Ba0.9Sr0.1)TiO3-xBi(Mg2/3Nb1/3)O3 lead-free ceramics with remarkable energy storage performance - Huang Xuechen; Dai Jinba; Liu Shulong; Li Wenlong; Li Yu; Cao Wenjun; Wang Chunchang (Processing and Application of Ceramics)
In this research, (1-x)(Ba0.9Sr0.1)TiO3-xBi(Mg2/3Nb1/3)O3 (BST-BMN, where x = 0, 0.06, 0.08, 0.12 and 0.20) powders were synthesized via a solid-state reaction method. The corresponding lead-free ceramics were obtained at the optimal sintering temperature. For x ≥ 0.06, the material formed dense, homogeneous pseudocubic perovskite structures. The increase of the BMN content induces strong relaxor behaviours with diffuse phase transition characteristics, enhancing the temperature stability of dielectric properties. Consequently, the ceramics exhibited narrow polarization-electric field (P-E) loops and superior energy storage capabilities. The composition 0.88BST-0.12BMN was found to be optimal, attributed to the improvement in breakdown field strength, yielding a recoverable energy density of 2.504 J/cm3 and an efficiency of 90.2%under an electric field strength of 250 kV/cm. Furthermore, this ceramic composition retains consistent energy storage across temperatures ranging from 20 to 120°C and frequencies from 1 to 100Hz, underscoring its potential for application in high-power pulsed capacitors.